HUBUNGAN ANTARA HARGA DIRI (SELF ESTEEM) DENGAN PRESTASI BELAJAR PADA SISWA SMKN 48 DI JAKARTA TIMUR - Neny Irawati; Nurahma Hajat (Jurnal Ilmiah Econosains, 2012)
ABSTRACTThe purpose of this research is to know the correlation between self esteem with learning achievement on student 48 Vocational School in East Jakarta.This research have been done for 4 months since February 2012 until May 2012. The method of research is survey method with correlation approach. The populations of this research is all of employee in 48 Vocational School in East Jakarta, which reach population is 60 person and the sample is 30 person with 5% wrong ability. Technic for getting sample is simple random proportional. For getting the data of variaele data X and Y was used likert sacle. The analysis test by finding regression equation, that is Å¶ =56,60 + 0,165X. After that data normality test is done by using lilliefors formula and the result was Lcount = 0,068 in significant level 0,05 and Ltable =0,124 , so Lcount < Ltable. Mean that the mistake of prediction regression Y to X had normal distribution. While regression linearity test, Fcount (0,94) <Ftable (2,11), showing that regression was linear. For regression significance test and the result was, Fcount (26,26)>Ftable (4,04). It shows it had significance regression. The result of product moment of correlations coefficient test was rxy = 0,591 continued by using correlations coefficient significance test with t-test. Counting result was, tcount = 5,12 while ttable = 1,68 and so, tcount > ttable. It means that there were significance and positive correlations between correlations self esteem with learning achievement. Beside that, the result of determination coefficient test was 34,89%, it means that learning achievement variable determined by 34,89% self esttem of student variable. The conclusion of the research has shown that there was a positive correlations self esteem with learning achievement on student.Key Words: Self Esteem, learning achievement